Assessing the Role of State and Local Public Health in Outreach and Enrollment for Expanded Coverage A Case Study on Illinois - Williams, Malcolm V. (RAND Corporation, 2016)
Part of a series highlighting innovative models and best practices for leveraging local health departments' involvement in Patient Protection and Affordable Care Act outreach and enrollment, this brief reports on a case study on Illinois that captures nuanced differences in how health departments support these efforts, identifies facilitators and barriers to these approaches, and develop lessons learned from these activities.